Effect of banana flour, screw speed and temperature on extrusion behaviour of corn extrudates - Kaur, Amritpal (J Food Sci Technol, 2014)
Effect of extrusion parameters (banana flour, screw speed, extrusion temperature) on extrusion behaviour of corn grit extrudates were studied. Second order quadratic equations for extrusion properties as function of banana flour (BF), screwspeed (SS) and extrusion temperature (ET) were computed. BF had predominant effect on the Hunter color (L*, a*, b*) parameters of the extrudates. Addition of BF resulted in corn extrudates with higher L* and lower a* and b* values. Higher ET resulted in dark colored extrudates with lower L* and a* value. Higher SS enhanced the lightness of the extrudates. Expansion of the extrudates increased with increase in the level of BF and ET. WAI of the extrudates decreased with BF whereas increased with SS. However, reversed effect of BF and SS on WSI was observed. Flextural strength of the extrudates increased with increase in SS followed by BF and ET. The addition of BF and higher ET resulted in extrudates with higher oil uptake.